Extracts of Thesium chinense inhibit SARS-CoV-2 and inflammation in vitro - Juncheng Ma; Juanru Wei; Gang Chen; Xiaowei Yan; Hechun Sun; Ning Li (Pharmaceutical Biology, 2023)
AbstractContext The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is still spreading rapidly. Relevant research based on the antiviral effects of Thesium chinense Turcz (Santalaceae) was not found.Objective To investigate the antiviral and anti-inflammatory effects of extracts of T. chinense.Materials and methods To investigate the anti-entry and replication effect of the ethanol extract of T. chinense (drug concentration 80, 160, 320, 640, 960 μg/mL) against the SARS-CoV-2. Remdesivir (20.74 μM) was used as positive control, and Vero cells were used as host cells to detect the expression level of nucleocapsid protein (NP) in the virus by real-time quantitative polymerase chain reaction (RT-PCR) and Western blotting. RAW264.7 cells were used as an anti-inflammatory experimental model under lipopolysaccharide (LPS) induction, and the expression levels of tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) were detected by enzyme-linked immunosorbent assay (ELISA).Results The ethanol extract of T. chinense significantly inhibited the replication (half maximal effective concentration, EC50: 259.3 μg/mL) and entry (EC50: 359.1 μg/mL) of SARS-CoV-2 into Vero cells, and significantly reduced the levels of IL-6 and TNF-α produced by LPS-stimulated RAW264.7 cells. Petroleum ether (EC50: 163.6 μg/mL), ethyl acetate (EC50: 22.92 μg/mL) and n-butanol (EC50: 56.8 μg/mL) extracts showed weak inhibition of SARS-CoV-2 replication in Vero cells, and reduced the levels of IL-6 and TNF-α produced by LPS-stimulated RAW264.7 cells.Conclusion T. chinense can be a potential candidate to fight SARS-CoV-2, and is becoming a traditional Chinese medicine candidate for treating COVID-19.